Small Cell Neuroendocrine Carcinoma of the Urinary Tract Successfully Managed with Neoadjuvant Chemotherapy. (18th August 2013) - Ahsaini, Mustapha; Riyach, Omar; Tazi, Mohammed Fadl; El Fassi, Mohammed Jamal; Farih, My Hassan; Elfatmi, Hind; Amarti, Afaf
Abstract : Introduction . Small cell neuroendocrine carcinomas of the urinary tract is an extremely rare entity and very few cases have been reported in the literature. Small cell neuroendocrine carcinoma of the urinary tract (SCC-UT) is the association between bladder and urinary upper tract-small cell carcinoma (UUT-SCC). It characterized by an aggressive clinical course. The prognosis is poor due to local or distant metastases, and usually the muscle of the bladder is invaded. Case Presentation . We report a rare case of a 54-year-old Arab male native of moroccan; he is a smoker and was referred to our institution for intermittent hematuria. Following a diagnosis of small cell neuroendocrine carcinomas of the ureter and the bladder, thoracoabdominal-pelvic CT was done, and the staging of the tumor was done in the bladder (T2N0M0) and (T1N0M0) in the ureter. Neoadjuvant alternating doublet chemotherapy with ifosfamide/doxorubicin and etoposide/cisplatin was realized, and nephroureterectomy associated to a cystoprostatectomy was carried out. After 24 months of followup, no local or distant metastasis was detected. Conclusion . The purpose of this review is to present a rare case of pure small cell neuroendocrine carcinoma of the urinary tract and review the literature about the place of neoadjuvant chemotherapy in this rare tumors.